Antimicrobial resistance and genomic characterization of Escherichia coli from pigs and chickens in Zhejiang, China - Zhou, Wei; Lin, Rumeng; Zhou, Zhijin; Ma, Jiangang; Lin, Hui; Zheng, Xue; Wang, Jingge; Wu, Jing; Dong, Yuzhi; Jiang, Han; Yang, Hua; Yang, Zhangnv; et al. (Frontiers in Microbiology, 2022)
Escherichia coli is considered an opportunistic pathogen and an indicator for antimicrobial resistance (AMR) monitoring. Despite many reports on its AMR monitoring, studies based on genome-based analysis of AMR genes are still insufficient. Here, 181 E. coli strains were isolated from anal swab samples collected from pigs and chickens of animal farms located in Eastern China and sequenced through the Illumina platform. The results showed that 87.85% (159/181) of the E. coli isolates were multidrug-resistant (MDR). Ampicillin (AMP)- spectinomycin (SPT)- tetracycline (TET)- florfenicol (FFC)- sulfisoxazole (SF)- trimethoprim/sulfamethoxazole (SXT) was the predominant AMR pattern. By whole-genome sequencing, we found that ST10 (10.49%, 19/181) and ST48 (7.18%, 13/181) were major sequence types. IncFIB and IncX1 were the most prevalent plasmid replicons. The AMR genes blaNDM-5 (1.10%, 2/181), mcr-1 (1.10%, 2/181), tet(X4) (1.10%, 2/181), and cfr (6.08%, 2/181) were also found in these isolates. In addition, among the 169 virulence genes detected, we identified astA (37.02%, 67/181), hlyA (1.66%, 3/181), hlyB (1.66%, 3/181) and hlyD (1.66%, 3/181), which were closely related to heat-stable enterotoxin 1 and α-hemolysin. In addition, there were 33 virulence genes associated with the iron uptake system, and 46 were adhesion-related genes. Our study highlighted the need for routine surveillance of AMR with advanced genomic approaches, providing up-to-date data on the prevalence of AMR for the development and execution of antimicrobial stewardship policy.